Os processos de referenciação em textos argumentativos - Sabaini, Mariam Tesch (2012)
This research highlights the role of benchmarking in the process of argumentative texts from the printed media. To do so, were explored and analyzed the elements of the editorial references, checking to what extent they are cohesive instrumental line of text, while also significant load argumentative. The corpus was selected two newspaper editorials, and as a criterion for choosing the theme. One was published in Folha de S. Paulo (FSP) on the date of February 1, 2012, and is entitled Challenges for Europe and the other was published in the newspaper Estado de Sao Paulo (ESP) on the date of February 24, 2012 and is entitled the Worsening Crisis in Europe. In both the editorial authors have used the processes of referral and argumentative maneuver to assert their opinions. The theoretical-methodological support adopted was developed from studies in textual language, privileging the cohesion and argument, based on the referral process. For this, we base in authors such as Koch (1996/2002), Koch / Elias (2010), Guimarães (2007), Marchuschi (2010), among others.